Availability and Utilization of Instructional Materials in Nursing Training Institutions in Anambra State - Okwuchukwu, Ezennakwe, Juliet; Chibuike, Ndie, Elkenak; Emenike, Anieche John (International Journal of Medical and Health Sciences Research, 2022)
This descriptive survey research assessed the availability and utilization of instructional materials in nursing training institutions in Anambra State. A sample size of 298 students and 50 teachers were randomly selected from four Nursing schools in Anambra State. Self-structured questionnaire was used for data collection. Inferential statistics was applied in testing the null hypotheses at 0.05 level of significant. Results revealed that student nurses and Teachers believed that instructional materials- Audio/Visual equipment (59.7% of students, 64.0% of teachers); Power point presentation (74.7% students, 58.0% teachers); Anatomical Models (98.0% Students, 80.2% Teachers); Medical Instruments (99.7% students, 96.0% teachers); Good demonstration rooms (95.7% students,86.0% teachers) were available in nursing training institutions in Anambra State. 73.6% Students and 74.0% Teachers indicated that these materials were often utilized by Tutors. Private/mission owned schools make more available (80.2% the students and 54.0% teachers) and utilize more (82.8% students, 62.0% teachers) instructional materials than the government owned schools. Significance difference (P <0.05) exists in the availability and utilization of instructional materials between university-based and hospital-based nursing schools as well as between private/mission-owned and government-owned schools. There is positive relationship (Rho= 0.603, P <0.000) between availability and utilization of instructional materials in nursing training. The study concluded that instructional materials were adequately available and often utilized by Tutors in nursing schools. The researchers recommended that incentives should be given to Nurse Educators who utilize instructional materials in other to encourage them.